2018
DOI: 10.4172/2472-1654.100120
|View full text |Cite
|
Sign up to set email alerts
|

An Intervention Study of Clinician-Patient Nonverbal Interactions and Patient Perceptions of Visits

Abstract: The aim of this study is to characterize the effects of specific clinician nonverbal behaviors on patient nonverbal interaction and perceptions of clinicians. A randomized controlled trial was conducted to evaluate the effects of clinician training on improving patient perceptions of the clinical visit. Two hundred and seventy one patients saw clinicians that they had no prior relationship with for cold symptoms. The clinicians were trained to interact with patients in either "standard" (type A) or "enhanced" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Moreover, video communication precludes physical touch, a component that may play a key role in perceptions of social support. Indeed, physical touch has been found to increase perceptions of empathy (Montague et al, 2013 ), reduce anxiety (Gagne and Toye, 1994 ), and buffer against stress (Coan et al, 2006 ). Previous research on quarantines, which limit physical touch between humans, has found increased anxiety, anger, and post-traumatic stress symptoms because of the quarantine (Brooks et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, video communication precludes physical touch, a component that may play a key role in perceptions of social support. Indeed, physical touch has been found to increase perceptions of empathy (Montague et al, 2013 ), reduce anxiety (Gagne and Toye, 1994 ), and buffer against stress (Coan et al, 2006 ). Previous research on quarantines, which limit physical touch between humans, has found increased anxiety, anger, and post-traumatic stress symptoms because of the quarantine (Brooks et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Psychotherapy in an analogue setting might facilitate building a reliable therapeutic alliance and expressing empathy, which is reflected by the psychotherapists’ ratings within the online survey. They explicitly criticised the lack of nonverbal communication through facial expressions and gestures in VCT, which is a crucial factor for therapeutic alliance (Klasen et al, 2013) and empathy (Kraft‐Todd et al, 2017; Montague et al, 2014; Pettit et al, 2019; Riess & Kraft‐Todd, 2014; Timmermann et al, 2017). Furthermore, they speculated that dealing with crisis and suicidality might be a problem in VCT, which does not allow comparable support to a face‐to‐face encounter.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding rapport, the PCCMC posits that clinicians' efforts to build a strong interpersonal relationship with patients are facilitated by approaching the encounter with the mindset of forming a therapeutic alliance and offering patients social and emotional support by demonstrating empathy and compassion for their unique illness experience. Attention to less obvious features of the medical interaction, such as the physical comfort of patients and where clinicians place themselves relative to the patient during the interaction, serve to create an atmosphere of warmth and reinforce effective communication through implicit and nonverbal behaviors, with evidence suggesting that eye gaze, nodding, and other cues of nonverbal attention are the strongest predictors of patient satisfaction (Arora, 2003; Frankel & Stein, 1999; Montague, 2018; Morse & Sweeny, 2020). Used together, robust evidence suggest these strategies serve to cultivate trust and strengthen patient–provider relationships, improving patient satisfaction, treatment adherence, and care continuity (Arora, 2003; Hillen et al, 2011; Rodriguez & Pellegrini, 2019; Sinaiko et al, 2019; Street, 2013; Street et al, 2013).…”
Section: Tying Up Loose Ends: the Person‐centered Communication Modelmentioning
confidence: 99%